Sand-carrying agent, preparation method thereof and water-based drilling fluid

By crosslinking polyvinyl alcohol and lignin to form a high mechanical strength gel sand carrying agent, the problems of sand carrying agent in the prior art have a great impact on the performance of the well slurry, the well wall instability and the viscosity at high temperature have been solved, and the efficient sand carrying and degradation ability has been improved.

CN120230519AActive Publication Date: 2025-07-01CHINA NAT PETROLEUM CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311839776.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-07-01
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

The existing sand carrying agents have an adverse impact on the performance of the original well slurry during drilling, causing the well wall to be instable, have poor use effect, and have a significant decrease in viscosity in high-temperature environments, making it difficult to avoid blockage while carrying sand efficiently.

Method used

Polyvinyl alcohol and lignin are crosslinked to form a gel sand carrying agent with high mechanical strength. By controlling the addition ratio of lignin and the use of the crosslinking agent glutaraldehyde, the mechanical properties and shear resistance of the sand carrying agent are improved, and the reaction activity and hydrophobicity of the lignin are modified by alkali treatment.

Benefits of technology

Maintain high viscosity and mechanical properties in high temperature environments, improve sand carrying capacity, avoid blockage problems, achieve clean and efficient sand carrying of the wellbore, and has good biodegradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120230519A_ABST
    Figure CN120230519A_ABST
Patent Text Reader

Abstract

The invention provides a sand-carrying agent, a preparation method thereof and a water-based drilling fluid. The sand-carrying agent comprises the following raw materials in parts by mass: 1-16000 parts of polyvinyl alcohol, 1-1000 parts of lignin, 1-8 parts of a cross-linking agent and 10-270 parts of water. The invention also provides a preparation method of the sand-carrying agent, which comprises the following steps: dissolving the polyvinyl alcohol and the lignin in water, and adding the cross-linking agent for reaction to obtain the sand-carrying agent. The invention also provides a water-based drilling fluid prepared from the sand-carrying agent. The sand-carrying agent provided by the invention has relatively high temperature resistance, mechanical strength, inhibition capability and sand-carrying capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield drilling fluid, in particular to a sand carrying agent and a preparation method thereof and a water-based drilling fluid. Background Art

[0002] Drilling fluid is a circulating flushing medium used in the drilling process, which can be divided into water-based drilling fluid, oil-based drilling fluid and gas drilling fluid. Water-based drilling fluid has the advantages of low cost, simple maintenance, wide range of treatment agents, easy performance control, and protection of oil and gas layers. It is a commonly used drilling fluid system in oilfield drilling. In high-angle well sections and horizontal well sections, the static sand suspension and dynamic rock carrying capacity of drilling fluid is a difficult point. Under the premise of certain drilling parameters such as drill bit assembly and wellbore trajectory design, and limited by the rated power of the ground unit, in order to achieve the maximum extension of the horizontal well section, it is necessary to achieve efficient rock carrying under low density, low displacement and low return speed conditions, keep the wellbore clean, reduce the friction torque of the drill bit as much as possible, and reduce the total circulation pressure loss. Rock carrying and sand removal of drilling fluid is one of the indispensable research objects in drilling engineering.

[0003] At present, the commonly used technical means at the drilling site is to pump in heavy slurry, thick slurry, and fiber sand cleaning fluid (less used) for circulating sand lifting. However, this technical means has major drawbacks: ① It has an adverse effect on the performance of the original well slurry. The increase of macromolecular polymers causes the slurry viscosity to increase, especially when used in high-density well slurry. The impact is more serious; ② It induces wellbore instability. When heavy slurry is used in the narrow density window well section, the formation stress is released under the action of external force, causing the wellbore to collapse; ③ The use effect is poor and the purpose of cleaning the wellbore cannot be achieved. When the thick slurry is pumped into the horizontal well section of the open hole, the flow pattern of the sand-carrying fluid in the horizontal section is mostly laminar flow, which cannot achieve the effect of turbulent rock carrying and sand cleaning, or can only move the cuttings to a certain distance and cannot carry them out; ④ Non-degradable fibers block the annulus or drilling tool water hole, and the gaps in the downhole tools or annulus are small and easy to block the gaps or channels.

[0004] Polyvinyl alcohol is a water-soluble polymer, which contains a large number of hydroxyl groups in its molecules, making it easily soluble in water and having excellent film-forming properties, adhesion, miscibility and chemical resistance. Although polyvinyl alcohol can form gel, it has insufficient mechanical strength and poor mechanical properties, and its sand-carrying capacity is not outstanding when used in sand-carrying agents.

[0005] Existing sand-carrying agents have the problems of adversely affecting the performance of the original well slurry, inducing well wall instability, having poor use effects, and being non-degradable. Summary of the invention

[0006] In order to solve the above problems, the object of the present invention is to provide a sand carrying agent and a preparation method thereof and a water-based drilling fluid.

[0007] To achieve the above object, the present invention provides a proppant. By mass, the raw materials of the proppant include: 1-16000 parts of polyvinyl alcohol, 1-1000 parts of lignin, 1-8 parts of crosslinking agent, and 10-270 parts of water.

[0008] In the above proppant, the polyvinyl alcohol and lignin can crosslink to form a gel proppant with high mechanical strength, improving the thickening ability and inhibition ability of the proppant.

[0009] In the above proppant, the polyvinyl alcohol includes one or a combination of two or more of polyvinyl alcohol 1788, polyvinyl alcohol 1799, polyvinyl alcohol 2688, and polyvinyl alcohol 2699.

[0010] In the above proppant, the lignin adopted in the present invention has the characteristics of being cheap and easily available and environmentally friendly compared with petroleum-based raw materials. The prepared proppant has low cost and is environmentally friendly. Lignin also has good biodegradability and low price, which can greatly reduce the production cost.

[0011] In the above proppant, the lignin is lignin treated with alkali, which can be called alkali lignin. In the lignin modified by alkali, lignin monomers are broken into small pieces, and the methoxy groups in the lignin molecular structure are removed and dissolved out as alkali lignin. Alkali lignin has relatively high reaction activity, low molecular weight and good hydrophobicity. The molecular weight of the lignin treated with alkali is 1000-2000 g / mol.

[0012] In the above proppant, the method of alkali treatment includes: mixing lignin with an alkali solution, reacting, filtering, and adjusting the pH value to 2-3 to obtain the solution of the lignin.

[0013] In the above method of alkali treatment, the pH value of the alkali solution is 10-13.

[0014] In the above method of alkali treatment, the reaction temperature can be 90-120 °C, such as specific values of 90 °C, 100 °C, 110 °C, 120 °C, etc. and ranges with any two of the above specific values as endpoints. The reaction time can be 20-30 h, such as 24 h.

[0015] In the above proppant, the above method of alkali treatment can specifically include: mixing lignin with an alkali solution, fully dissolving lignin in an alkali solution with a pH value of 10-13 to form a mixed solution, reacting, filtering the mixed solution to remove insoluble impurities, then adjusting the pH value of the filtrate to 2-3, centrifuging (the rotation speed can be 8000 rpm), washing the centrifugal precipitate three times with deionized water, and drying to obtain the lignin.

[0016] In the above-mentioned proppant, by controlling the addition ratio of lignin, the mechanical ability of the proppant can be regulated, and the effective regulation of the shear resistance ability can be achieved. In some specific embodiments, the mass ratio of the polyvinyl alcohol to the lignin is generally 1 - 16000:1 - 1000, and further can be controlled to 300 - 2000:12 - 220.

[0017] In the above-mentioned proppant, the cross-linking agent may include glutaraldehyde cross-linking agent. By using cross-linking agents such as glutaraldehyde, the gel formed by cross-linking lignin and polyvinyl alcohol has the characteristics of high cross-linking density and high cross-linking strength.

[0018] In the above-mentioned proppant, the mass ratio of the cross-linking agent to the polyvinyl alcohol may be 1 - 8:300 - 2000.

[0019] In the above-mentioned proppant, the mass ratio of the water to the polyvinyl alcohol is generally 10 - 270:1 - 16000, and further can be controlled to 20 - 270:300 - 2000, 10 - 200:300 - 2000.

[0020] In some specific embodiments, by mass, the raw materials of the proppant may include: 300 - 2000 parts of polyvinyl alcohol, 12 - 220 parts of lignin, 1 - 8 parts of cross-linking agent, and 20 - 270 parts of water.

[0021] The above-mentioned proppant obtained by the present invention can be used as a lignin-modified polyvinyl alcohol proppant.

[0022] The present invention also provides a preparation method of the above-mentioned proppant, and the preparation method includes: dissolving polyvinyl alcohol and lignin in water, adding a cross-linking agent for reaction to obtain the proppant.

[0023] In the above-mentioned preparation method, the temperature of the reaction can be controlled to 70 - 90°C, specifically, it can be specific values such as 70°C, 75°C, 80°C, 85°C, 90°C, etc. and ranges with any two of the above specific values as endpoints.

[0024] In the above-mentioned preparation method, the reaction time can be controlled to 30 min - 40 min, specifically, it can be specific values such as 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min, 40 min, etc. and ranges with any two of the above specific values as endpoints.

[0025] In the above-mentioned preparation method, when the polyvinyl alcohol and lignin are dissolved in water to form a mixed solution, the mixed solution can be heated to 80 - 90°C to promote the dissolution of lignin.

[0026] The raw materials of the above preparation method provided by the present invention are simple in variety and wide in source, the production operation is simple, the reaction conditions are mild, the prepared product has excellent performance, and it is convenient for large-scale production and popularization and application.

[0027] The present invention also provides an aqueous drilling fluid, which is made of the above-mentioned sand-carrying agent. The aqueous drilling fluid made of the above-mentioned sand-carrying agent can maintain a relatively high viscosity and mechanical ability even in a high-temperature drilling environment, and has relatively high shear resistance and inhibition ability.

[0028] The beneficial effects of the present invention are as follows:

[0029] 1. The sand-carrying agent provided by the present invention is prepared by blending and cross-linking polymerization of lignin and polyvinyl alcohol, which can effectively improve the mechanical properties, shear resistance and inhibition ability of the sand-carrying agent.

[0030] 2. Conventional polyvinyl alcohol sand-carrying agents will show a significant decrease in viscosity or even degradation in a high-temperature drilling environment, resulting in a great reduction in the sand-carrying ability. The sand-carrying agent provided by the present invention can withstand a high-temperature drilling environment, can maintain a viscosity and mechanical property higher than that of polyvinyl alcohol at 80°C, and improves the sand-carrying ability of the sand-carrying agent at high temperature.

[0031] 3. The sand-carrying agent provided by the present invention has good degradation ability, which can avoid the problem of the sand-carrying agent blocking the drill tool or the hole. Description of the Drawings

[0032] Figure 1 Test results of the storage modulus and loss modulus of the sand-carrying agent of Comparative Example 1.

[0033] Figure 2 Test results of the storage modulus and loss modulus of the sand-carrying agent of Example 1.

[0034] Figure 3 Graph of the relationship between the viscosity and angular frequency of the sand-carrying agent of Comparative Example 1.

[0035] Figure 4 Graph of the relationship between the viscosity and temperature of the sand-carrying agent of Comparative Example 1.

[0036] Figure 5 Graph of the relationship between the viscosity and angular frequency of the sand-carrying agent of Example 1.

[0037] Figure 6 Graph of the relationship between the viscosity and temperature of the sand-carrying agent of Example 1.

[0038] Figure 7 Graph of the relationship between the viscosity and angular frequency of the sand-carrying agent of Example 1 after heating for 3 h.

[0039] Figure 8 Graph of the relationship between the viscosity and angular frequency of the sand-carrying agent of Example 1 after heating for 120 h. Detailed implementation mode

[0040] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention will be described in detail below, but it should not be construed as a limitation on the scope of implementation of the present invention.

[0041] Example 1

[0042] This example provides a proppant, and the preparation method of the proppant includes:

[0043] (1) Alkaline treatment of lignin: 10 g of lignin is added to an aqueous NaOH solution with a concentration of 2 mol / L, and the reaction is carried out at 100 °C for 24 hours to fully dissolve the lignin. The solution is filtered to remove insoluble impurities. Further, a saline solution is added to the filtrate to adjust the pH value to 2, and centrifuged at 8000 rpm. The precipitate is washed three times with deionized water and dried in a vacuum oven to obtain lignin.

[0044] (2) By mass, 2000 parts of polyvinyl alcohol 1799, 80 parts of the lignin obtained in step (1), and 100 parts of water are stirred at 90 °C for 3 h until completely dissolved, and then 8 parts of glutaraldehyde crosslinking agent is added, and crosslinking reaction is carried out at 80 °C for 30 min, and cooled to obtain a proppant, and this proppant is a lignin-modified polyvinyl alcohol proppant.

[0045] Example 2

[0046] This example provides a proppant, and the preparation method of the proppant includes:

[0047] (1) Alkaline treatment of lignin: 10 g of lignin is added to an aqueous NaOH solution with a concentration of 2 mol / L, and the reaction is carried out at 100 °C for 24 hours to fully dissolve the lignin. The solution is filtered to remove insoluble impurities. Further, a saline solution is added to the filtrate to adjust the pH value to 2, and centrifuged at 8000 rpm. The precipitate is washed three times with deionized water and dried in a vacuum oven to obtain lignin.

[0048] (2) By mass, 1000 parts of polyvinyl alcohol 1799, 220 parts of the lignin obtained in step (1), and 270 parts of water are stirred at 90 °C for 3 h until completely dissolved, and then 8 parts of glutaraldehyde crosslinking agent is added, and crosslinking reaction is carried out at 80 °C for 30 min, and cooled to obtain a proppant, and this proppant is a lignin-modified polyvinyl alcohol proppant.

[0049] Example 3

[0050] This example provides a proppant, and the preparation method of the proppant includes:

[0051] (1) Alkaline treatment of lignin: 10 g of lignin was added to an aqueous NaOH solution with a concentration of 2 mol / L, and the reaction was carried out at 100 °C for 24 hours to fully dissolve the lignin. The solution was filtered to remove insoluble impurities. Further, an aqueous salt solution was added to the filtrate to adjust the pH value to 2, and then centrifuged at 8000 rpm. The precipitate was washed three times with deionized water and dried in a vacuum oven to obtain lignin.

[0052] (2) By mass, 300 parts of polyvinyl alcohol 1799, 12 parts of lignin, and 20 parts of water were stirred at 90 °C for 3 h until completely dissolved. Then, 1 part of glutaraldehyde cross-linking agent was added, and the cross-linking reaction was carried out at 80 °C for 30 min. After cooling, a proppant was obtained, and this proppant was a lignin-modified polyvinyl alcohol proppant.

[0053] Comparative Example 1

[0054] This comparative example provides a proppant, and the preparation method of this proppant includes:

[0055] By mass, 2000 parts of polyvinyl alcohol 1799 and 100 parts of water were stirred at 90 °C for 3 h until completely dissolved. Then, 8 parts of glutaraldehyde cross-linking agent was added, and stirred at 80 °C for 1 - 2 min. After cooling, a proppant was obtained, and this proppant was a polyvinyl alcohol proppant.

[0056] Test Example

[0057] This test example provides the performance test results of the above examples and comparative examples.

[0058] 1. Viscoelasticity test

[0059] Using an American Discovery HR-2 rheometer, frequency scanning was used to measure the relationship between the storage modulus, loss modulus and shear rate of the polyvinyl alcohol proppant and the lignin-modified polyvinyl alcohol proppant. The relationship between the storage modulus, loss modulus and angular frequency of the polyvinyl alcohol proppant in Comparative Example 1 was measured as shown in Figure 1 shown, and the data of the lignin-modified polyvinyl alcohol proppant in Example 1 was measured as shown in Figure 2 shown. By comparing Figure 1 and Figure 2 , it can be seen that lignin modification can greatly improve the storage modulus and loss modulus of the proppant, making it have higher mechanical strength. The sand needs a longer time to settle in the proppant sample of Example 1, and it has better proppant-carrying performance.

[0060] 2. Viscosity test

[0061] Using an American Discovery HR-2 rheometer, the temperature ramp mode was used to measure the relationship between the viscosity of the sample and the shear rate and temperature. The relationship between the viscosity of the polyvinyl alcohol proppant and the angular frequency and temperature was measured as shown in Figure 3 andFigure 4 As shown, the data of the lignin-modified polyvinyl alcohol of Example 1 are as follows Figure 5 and Figure 6 shown. Figure 5 The complex viscosity corresponding to the angular frequency of 100 rad / S in it is 77 Pa·s.

[0062] Figures 3 to 6 It can be seen that although the proppant with lignin shows shear thinning, when the shear rate is in the range of 0.1 to 100 / s, the viscosity of the lignin-modified proppant is much greater than that of the proppant without lignin, and the lignin-modified proppant has stronger shear resistance.

[0063] From Figures 3 to 6 it can be seen that the viscosity of the proppant of Example 1 in an environment with a higher angular frequency and a higher temperature is higher than that of the proppant of Comparative Example 1, indicating that the proppant of Example 1 has better temperature resistance. When the temperature rises, it can still maintain a relatively high viscosity level and mechanical properties, and the sand-carrying capacity of the proppant is significantly improved.

[0064] Figure 7 and Figure 8 are the graphs of the relationship between the viscosity and the angular frequency of the proppant of Example 1 after heating for 3 h and 120 h. Figure 7 The complex viscosity corresponding to the angular frequency of 100 rad / S in it is 72 Pa·s; Figure 8 The complex viscosity corresponding to the angular frequency of 100 rad / S in it is 23 Pa·s. From Figure 7 and Figure 8 it can be seen that the proppant has good degradation ability.

[0065] The above results show that the proppant provided by the present invention can effectively improve the mechanical properties, shear resistance and inhibition ability of the proppant through the copolymerization and crosslinking of lignin and polyvinyl alcohol. This proppant can withstand high-temperature drilling environments, can maintain a viscosity and mechanical properties higher than those of polyvinyl alcohol at 80°C, and has good degradation ability, which can avoid the problem of the proppant blocking the drill tool or the pore channel.

Claims

1. A proppant, calculated by mass, the raw materials of the proppant include: 1 - 16000 parts of polyvinyl alcohol, 1 - 1000 parts of lignin, 1 - 8 parts of cross - linker, 10 - 270 parts of water.

2. The proppant according to claim 1, wherein The cross - linker includes glutaraldehyde cross - linker.

3. The proppant according to claim 1, wherein, The polyvinyl alcohol includes one or a combination of two or more of polyvinyl alcohol 1788, polyvinyl alcohol 1799, polyvinyl alcohol 2688, and polyvinyl alcohol 2699.

4. The proppant according to claim 1, wherein, The lignin is lignin treated with alkali. The method of alkali treatment includes: mixing lignin with an alkali solution, reacting, filtering, and adjusting the pH value to 2 - 3 to obtain the solution of the lignin.

5. The proppant according to claim 4, wherein, The molecular weight of the lignin treated with alkali is 1000 - 2000 g / mol.

6. The proppant according to claim 4, wherein The pH value of the alkali solution is 10 - 13.

7. The proppant according to claim 1, wherein, The mass ratio of the polyvinyl alcohol to the lignin is 300 - 2000:12 - 220.

8. The proppant according to claim 1, wherein The mass ratio of the cross - linker to the polyvinyl alcohol is 1 - 8:300 - 2000.

9. The preparation method of the proppant according to any one of claims 1 - 8, and the preparation method includes: Dissolving polyvinyl alcohol and lignin in water, adding a cross - linker for reaction to obtain the proppant.

10. The preparation method according to claim 9, wherein The temperature of the reaction is 70 - 90 °C, and the time of the reaction is 30 min - 40 min.

11. An aqueous drilling fluid, which is made of the proppant according to any one of claims 1 - 8.

Citation Information

Patent Citations

  • Cellulose blended modified polyvinyl alcohol fracturing fluid and preparation method thereof

    CN104974739A

  • Weak gel tackifier for drilling fluid and preparation method of weak gel tackifier

    CN113372887A

  • Clean environment-friendly high-temperature-resistant nano fracturing fluid and preparation method thereof

    CN113583652A

  • Lignin derivatives based drilling fluid additive

    US20200087562A1